2016
DOI: 10.1186/s12877-016-0342-y
|View full text |Cite
|
Sign up to set email alerts
|

Environmental risk factors for dementia: a systematic review

Abstract: BackgroundDementia risk reduction is a major and growing public health priority. While certain modifiable risk factors for dementia have been identified, there remains a substantial proportion of unexplained risk. There is evidence that environmental risk factors may explain some of this risk. Thus, we present the first comprehensive systematic review of environmental risk factors for dementia.MethodsWe searched the PubMed and Web of Science databases from their inception to January 2016, bibliographies of rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
197
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(207 citation statements)
references
References 103 publications
3
197
0
7
Order By: Relevance
“…For example, in a meta-analysis of studies seeking links between suspected environmental agents and the risk of AD in humans, moderate-to-strong potential associations were found for such factors as air pollution, aluminum, silicon, selenium, pesticides, vitamin D deficiency, and electric and magnetic fields [104] (although the list of potential environmental factors is much longer, and the ability of epidemiological studies to identify them with certainty is limited). Myriad genetic polymorphisms appear to influence the odds of developing AD [105], but (except for the APOE type, above) the impact of individual genetic variants is small.…”
Section: Why Has Ad Not Been Identified In Nonhuman Species?mentioning
confidence: 99%
“…For example, in a meta-analysis of studies seeking links between suspected environmental agents and the risk of AD in humans, moderate-to-strong potential associations were found for such factors as air pollution, aluminum, silicon, selenium, pesticides, vitamin D deficiency, and electric and magnetic fields [104] (although the list of potential environmental factors is much longer, and the ability of epidemiological studies to identify them with certainty is limited). Myriad genetic polymorphisms appear to influence the odds of developing AD [105], but (except for the APOE type, above) the impact of individual genetic variants is small.…”
Section: Why Has Ad Not Been Identified In Nonhuman Species?mentioning
confidence: 99%
“…Studies also reported the impact of air pollution on children's health including raised incidence of respiratory symptoms in children, preterm delivery, and low birth weight . Exposure to heavy metals has been well documented to adversely impact neurological development and cognitive function in children and elderly has been well documented . Recent attention has been focused on the tens of thousands of synthetic chemicals that are in commerce today, many of which have been shown to disrupt endocrine function.…”
Section: Introductionmentioning
confidence: 99%
“…5 Exposure to heavy metals has been well documented to adversely impact neurological development and cognitive function in children and elderly has been well documented. 6,7 Recent attention has been focused on the tens of thousands of synthetic chemicals that are in commerce today, many of which have been shown to disrupt endocrine function. Exposure to endocrine disrupting chemicals has been linked to reduced reproduction and fertility, increased child neurodevelopmental disorders, increased obesity and diabetes, endocrine-related cancers, and other effects.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have suggested that excessive alcohol consumption, smoking, environmental toxin such as pesticides (Dichlorodiphenyltrichloroethane or DDT), food additives (such as nitrogen-based chemicals which are converted to toxic nitrosamines during cooking), contamination ( mussels contaminated with demonic acid), food components (two amino acids in seeds of certain legumes which enhance the action of the neurotransmitter glutamate), air pollution (such as aerosolized nickel nanoparticles, a component of air pollution) may also play important roles in the development of the disease [1]. Serious head injury, heart disease, diabetes, stroke, high blood pressure and high cholesterol which damage the heart and blood vessels may be indirectly related to the development of AD due to the increase of β-amyloid (Aβ).Recent systematic review of bibliographic databases from PubMed, EMBASE, Cochrane Library and Web of Science suggests that occupational exposure to extremely low frequency magnetic fields (ELF-MF) to welders, electric utility workers, train drivers and sewing machine operators may increase the risk of AD [2,3]. Experimental studies indicated that low-dose radiation exposures (10 cGy) induced genes not affected by high-dose radiation (2 Gy) and that low-dose genes were associated with unique pathways and functions.…”
mentioning
confidence: 99%
“…Recent systematic review of bibliographic databases from PubMed, EMBASE, Cochrane Library and Web of Science suggests that occupational exposure to extremely low frequency magnetic fields (ELF-MF) to welders, electric utility workers, train drivers and sewing machine operators may increase the risk of AD [2,3]. Experimental studies indicated that low-dose radiation exposures (10 cGy) induced genes not affected by high-dose radiation (2 Gy) and that low-dose genes were associated with unique pathways and functions.…”
mentioning
confidence: 99%